Analisis Dampak Penerapan Sistem ERP dalam Meningkatkan Kinerja PT Unilever Indonesia (UNVR) - Mar’ah Khoiru Qudwah; Gustina Masitoh (Yayasan Literasi Sains Indonesia, 2024)
Estimates companies link evidence technology ahead of looming collection of internal determinations in possession of commercial victims. One of them is the change of the company's term principal to an integrated principal, namely the principal of enterprise resource planning. This research was shown before explaining the effect of rupture of the main ERP operation, using a principal near four modules, the part in intensifying the power of PT Unilever Indonesia (UNVR). UNVR creates manufacturing companies that practice production, marketing, and quotas of consumer tools. The analysis method applied is that the literature uses secondary input points to break journal items, the company's annual demands, and parties that releven use the reference to analysis. Based on the reaction to the discussion, it was determined that UNVR linked SAP principal ahead of implementing savings near the implementation of provision and practicing work that was efficient in the SAP principal amount. On the day of initiation of SAP principal operations and continuous reactualization of principals SAP principal estimates intensify the qualifications of planning, organizing inputs, and inayat close to UNVR customers. The innovation of changing the breakdown of the term principal to the SAP principal is expected to be useful for UNVR ahead of the next period of commercial progress.